Solid oxide fuel cell and manufacturing method thereof

JP2025031193APending Publication Date: 2025-03-07HITACHI LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023137247
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-25
Publication Date
2025-03-07

AI Technical Summary

Benefits of technology

【0014】 一実施の形態によれば、固体酸化物型燃料電池の発電効率を向上できる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025031193000001_ABST
    Figure 2025031193000001_ABST
Patent Text Reader

Abstract

To provide a technology that can reduce the thickness of an electrolyte membrane while preventing the inclusion of defects and controlling the thickness with high precision, and can accommodate a large area of the electrolyte membrane, thereby improving the power generation efficiency of solid oxide fuel cells.SOLUTION: A solid oxide fuel cell 100 includes a porous insulating substrate 1, an anode electrode 2 formed on the porous insulating substrate 1, a solid electrolyte membrane 3 formed on the anode electrode 2, and a cathode electrode 5 formed on the electrolyte membrane 3. The electrolyte membrane 3 is a stabilized zirconia membrane to which rare earth elements are added, and is an anodized barrier membrane.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a solid oxide fuel cell and a method for manufacturing the same, and more particularly to a solid oxide fuel cell using stabilized zirconia to which rare earth elements are added as an electrolyte membrane, and a method for manufacturing the same. [Background technology]

[0002] In recent years, fuel cells have been attracting attention as a low-pollution, highly efficient power generation method. Fuel cells can be used as a power source for large-scale power generation systems or electric vehicles. Oxygen that enters the fuel cell from the atmosphere receives electrons at the cathode electrode and becomes oxygen ions. The oxygen ions move through the electrolyte membrane and release electrons at the anode electrode, where they react with hydrogen to become water. This series of processes allows an electric current to flow from the anode electrode to an external circuit.

[0003] In particular, solid oxide fuel cells (SOFCs) have a solid oxide electrolyte membrane that allows oxygen ions to pass through (ionic conductivity). By using a solid electrolyte membrane instead of a liquid, the configuration of the power generation system is simplified and maintenance is also easier.

[0004] For example, Patent Document 1 discloses the use of yttria stabilized zirconia (YSZ), which is a solid oxide, as an electrolyte membrane. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2015-176774 A Summary of the Invention [Problem to be solved by the invention]

[0006] The power generation efficiency of SOFCs is superior among fuel cells, but it is particularly efficient when operating at high temperatures, for example at around 1000°C. However, for practical use of SOFCs, operation at lower temperatures is required. However, lowering the temperature also reduces the amount of power that can be obtained. Therefore, it is necessary to reduce resistance losses by thinning the electrolyte membrane and improve power generation efficiency.

[0007] One method for manufacturing YSZ is thick-film printing using a sintered paste. Although this method can produce a large YSZ surface area of ​​approximately 10 cm square, the thickness of the YSZ is only a few micrometers, making it difficult to produce a thin film.

[0008] Another method for producing YSZ is a method using vacuum film formation. Examples of vacuum film formation include a method using an alloy target and reactive sputtering, a method using a ceramic target and sputtering, a method using CVD (Chemical Vapor Deposition), and a method using ALD (Atomic Layer Deposition). These methods can form YSZ with a thickness of 10 nm to 1 μm, but the area of ​​the YSZ is limited to a small area of ​​about a few mm square.

[0009] In addition, the YSZ obtained by the above-mentioned vacuum deposition method deviates from the stoichiometric composition, so it is necessary to crystallize it by high-temperature oxidation after deposition. Even if the coating by vacuum deposition is perfect, the inclusion of electrical defects that cause poor insulation is inevitable. The effect of defects becomes more pronounced as the area and thickness of the YSZ are increased. As a result, there is a limit to the thickness and area that can be obtained by vacuum deposition. This makes it difficult to put thin-film SOFCs into practical use.

[0010] The main objective of the present application is to provide a technology that can reduce the thickness of an electrolyte membrane while preventing the inclusion of defects and controlling the thickness with high precision, and can accommodate an increase in the area of ​​the electrolyte membrane, thereby improving the power generation efficiency of solid oxide fuel cells.

[0011] Other objects and novel features will become apparent from the description of this specification and the accompanying drawings. [Means for solving the problem]

[0012] A solid oxide fuel cell according to one embodiment includes a porous insulating substrate, an anode electrode formed on the porous insulating substrate, a solid electrolyte membrane formed on the anode electrode, and a cathode electrode formed on the electrolyte membrane. The electrolyte membrane is a stabilized zirconia membrane doped with rare earth elements and also an anodization barrier membrane.

[0013] A method for manufacturing a solid oxide fuel cell according to one embodiment includes the steps of: (a) preparing a porous insulating substrate, (b) forming an anode electrode on the porous insulating substrate, (c) forming a rare earth element-doped zirconium alloy film on the anode electrode, (d) forming a solid electrolyte membrane by anodizing the zirconium alloy film, and (e) forming a cathode electrode on the electrolyte membrane. The electrolyte membrane is a rare earth element-doped stabilized zirconia membrane and an anodization barrier membrane. Effect of the Invention

[0014] According to one embodiment, the power generation efficiency of a solid oxide fuel cell can be improved. [Brief description of the drawings]

[0015] [Figure 1] 1 is a cross-sectional view showing a solid oxide fuel cell in a first embodiment. [Diagram 2] 2 is an enlarged cross-sectional view showing a part of the porous insulating substrate in the first embodiment. [Diagram 3] 1A to 1C are cross-sectional views illustrating a method for manufacturing a solid oxide fuel cell in the first embodiment. [Figure 4] 4 is a cross-sectional view showing the method for producing a solid oxide fuel cell subsequent to FIG. 3. [Diagram 5]5 is a cross-sectional view showing the method for producing a solid oxide fuel cell subsequent to FIG. 4. [Figure 6] 1 is a plan view showing a jig used in a method for producing a solid oxide fuel cell in accordance with a first embodiment. [Figure 7] 4 is a graph showing current and voltage during anodizing treatment in the first embodiment. [Figure 8] 5A to 5C are cross-sectional views showing a method for manufacturing a solid oxide fuel cell in accordance with a second embodiment. [Figure 9] 9 is a cross-sectional view showing the method for producing a solid oxide fuel cell subsequent to FIG. 8. [Figure 10] 10 is a cross-sectional view showing the method for producing a solid oxide fuel cell subsequent to FIG. 9. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] Hereinafter, the embodiments will be described in detail with reference to the drawings. In all the drawings for explaining the embodiments, the same reference numerals are used for the members having the same functions, and the repeated explanations are omitted. In the following embodiments, the explanations of the same or similar parts will not be repeated as a rule unless it is particularly necessary.

[0017] In addition, the X-direction, Y-direction, and Z-direction described in this application intersect with each other and are perpendicular to each other. In this application, the Z-direction is described as the up-down direction, height direction, or thickness direction of a structure. In addition, expressions such as "plan view" or "planar view" used in this application mean that a surface formed by the X-direction and the Y-direction is a "plane" and this "plane" is viewed from the Z-direction.

[0018] (Embodiment 1) <Structure of solid oxide fuel cell> A solid oxide fuel cell (SOFC) 100 in the first embodiment will be described below with reference to Figures 1 and 2. As shown in Figure 1, the solid oxide fuel cell 100 includes a porous insulating substrate 1, an anode electrode 2, a solid electrolyte membrane 3, a conductive oxide membrane 4, and a cathode electrode 5.

[0019] Oxygen (O2) contained in the air enters the solid oxide fuel cell 100, receives electrons at the cathode electrode 5, and is converted into oxygen ions (O - The oxygen ions move through the conductive oxide film 4 and the electrolyte membrane 3, release electrons at the anode electrode 2, and react with hydrogen (H2) to become water (H2O). As the oxygen ions pass through the solid oxide fuel cell 100, a current can be passed from the anode electrode 2 to an external circuit.

[0020] The porous insulating substrate 1 is a substrate containing, for example, anodized aluminum, and formed by performing an anodization process that provides a porous coating on aluminum. As shown in FIG. 2, a plurality of holes 1a are formed in the porous insulating substrate 1. A conductive film 1b is formed on the surfaces of the plurality of holes 1a. The conductive film 1b contains, for example, Pt or Ni. The thickness of the porous insulating substrate 1 is, for example, 80 μm or more and 120 μm or less. The diameter of the hole 1a is, for example, 100 nm or more and 150 nm or less.

[0021] By covering the porous insulating substrate 1 with the conductive film 1b, the porous insulating substrate 1 can also be used as a part of the anode electrode 2. Furthermore, the conductive film 1b is formed thin so as not to fill the inside of each hole 1a, so that hydrogen can pass through the porous insulating substrate 1. The thickness of the conductive film 1b is, for example, 10 nm or more and 20 nm or less.

[0022] The anode electrode 2 is formed on the porous insulating substrate 1. The anode electrode 2 is made of a porous metal film and contains a transition metal. The transition metal is, for example, Ni. As will be described later, when the solid oxide fuel cell 100 generates power, it is exposed to high-temperature water vapor, for example, at 500°C. Therefore, the anode electrode 2 is required to have high heat resistance and oxidation resistance. The thickness of the anode electrode 2 is, for example, 50 nm or more and 500 nm or less. Note that, as shown in a modified example described later, the anode electrode 2 may contain a precious metal such as Pt.

[0023] The electrolyte membrane 3 is formed on the anode electrode 2. The electrolyte membrane 3 is a stabilized zirconia membrane having a property of passing oxygen ions (ionic conductivity) and having a rare earth element added thereto. The rare earth element is, for example, Y, Sc, Yb, Er, Dy or Gd. The rare earth element is most preferably Y. In particular, the yttria stabilized zirconia (YSZ) of the electrolyte membrane 3 has the chemical composition (Y2O3) X (ZrO2) 1-X It is most preferable that the electrolyte membrane 3 is 8YSZ, where X=8% in the above formula. The electrolyte membrane 3 is an anodized barrier membrane formed by anodizing the zirconium alloy membrane to which the rare earth element is added.

[0024] The conductive oxide film 4 is formed on the electrolyte membrane 3. The conductive oxide film 4 is, for example, a GDC film (CeO2 film with added Gd2O3), an LSC film ((La, Sr)CoO3 film), an LSFC film ((La, Sr)(Co, Fe)O3 film), or a BSCF film ((Ba, Sr)(Co, Fe)O3 film). In addition, when the solid oxide fuel cell 100 operates at a low temperature of 300°C or less, an ITO film (an inorganic mixture of In2O3 and SnO2) can also be used as the conductive oxide film 4.

[0025] In the solid oxide fuel cell 100 in the first embodiment, the conductive oxide film 4 is not essential. However, the conductive oxide film 4 has a property of transmitting oxygen ions and electrons, and is provided for the purpose of promoting the ionization of oxygen. By providing the conductive oxide film 4, the generation efficiency of oxygen ions can be improved, and the power generation efficiency can be improved.

[0026] The cathode electrode 5 is formed on the electrolyte membrane 3 via the conductive oxide film 4. The cathode electrode 5 contains, for example, Ni or Pt. The thickness of the cathode electrode 5 is, for example, not less than 50 nm and not more than 150 nm.

[0027] As described above, the electrolyte membrane 3 is an anodized barrier film formed by anodizing. In the anodizing process that provides a barrier film, the thickness of the oxide film formed is highly uniform, and local defects are automatically repaired. Therefore, the anodized barrier film finally obtained has a uniform thickness and is an oxide film without defects. The thickness of the electrolyte membrane 3 thus obtained is, for example, 10 nm or more and 500 nm or less. The area of ​​the electrolyte membrane 3 is about 10 cm square.

[0028] Thus, according to the first embodiment, it is possible to make the electrolyte membrane 3 thinner and to accommodate a larger area of ​​the electrolyte membrane 3. Therefore, the power generation efficiency of the solid oxide fuel cell 100 can be improved.

[0029] Below is described the relationship between the operating temperature of the solid oxide fuel cell 100 and the power obtained. Note that the following power is a calculated value when the rare earth element added to the electrolyte membrane 3 is Y, the electrolyte membrane 3 is made of the above-mentioned 8YSZ single crystal, and the thickness of the electrolyte membrane 3 is 10 nm.

[0030] At an operating temperature of 450°C, the available power is 6.7×10 1 W / cm 2 When the operating temperature is 400°C, the power that can be obtained is about 2.0×10 1 W / cm 2 At an operating temperature of 350°C, the power output is expected to be 5.8W / cm 2 At an operating temperature of 300°C, the power output is expected to be about 1.3W / cm 2 You can expect a degree of.

[0031] <Method of manufacturing solid oxide fuel cells> Each manufacturing step included in the method for manufacturing the solid oxide fuel cell 100 will be described below with reference to FIGS.

[0032] As shown in Fig. 3, first, a porous insulating substrate 1 is prepared. Next, a conductive film 1b is formed on the surfaces of the multiple holes 1a formed in the porous insulating substrate 1 by a film formation process using, for example, an ALD method (see Fig. 2). The conductive film 1b is formed so as not to fill the insides of the holes 1a.

[0033] Next, the anode electrode 2 is formed by sputtering on the porous insulating substrate 1. This sputtering is performed, for example, under a film formation pressure of 10 Pa or more and 15 Pa or less. The anode electrode 2 thus formed is made of a porous metal film.

[0034] Next, a zirconium alloy film 3a to which a rare earth element is added is formed on the anode electrode 2 by a sputtering method. The rare earth element is, for example, Y, Sc, Yb, Er, Dy or Gd. The rare earth element is most preferably Y. This sputtering method is performed at a film formation pressure lower than that of the sputtering method of the anode electrode 2, for example, under a film formation pressure of 0.5 Pa or more and 1.0 Pa or less. The zirconium alloy film 3a thus formed is not a porous film but a dense continuous film with a substantially uniform thickness.

[0035] For example, if the sputtering method of the zirconium alloy film 3a is performed at high pressure like the sputtering method of the anode electrode 2, the zirconium alloy film 3a grows as columnar crystals and becomes porous. Then, in the subsequent anodization treatment, oxidation proceeds along the grain boundaries of the columnar crystals, and the thickness of the electrolyte film becomes non-uniform. Therefore, it is difficult to obtain a good quality electrolyte film.

[0036] The electrolyte membrane 3 is formed from the zirconium alloy film 3a by the subsequent anodization process, but in consideration of the thickness consumed by the anodization, the thickness variation and the oxidation margin, the thickness of the zirconium alloy film 3a is set to be thicker than the desired thickness of the electrolyte membrane 3. For example, when the desired thickness of the electrolyte membrane 3 is 10 nm or more and 500 nm or less, the thickness of the zirconium alloy film 3a is set to be about 10% thicker than the desired thickness of the electrolyte membrane 3.

[0037] 4, the zirconium alloy film 3a is anodized to form a solid electrolyte film 3. The electrolyte film 3 is a stabilized zirconia film to which a rare earth element is added, similar to the zirconium alloy film 3a, and also serves as an anodization barrier film.

[0038] Fig. 6 is a plan view showing a jig 40 used in the anodization treatment. The chamber region 30, the oxidation region 31, and the alloy region 32 shown in Fig. 6 are each a part of the zirconium alloy film 3a. The oxidation region 31 is a region where the zirconium alloy film 3a is anodized, and the chamber region 30 is a part of the oxidation region 31, and is a region that substantially functions as a solid oxide fuel cell 100. In other words, the cross-sectional view of the chamber region 30 corresponds to Figs. 1, 3, 4, and 5.

[0039] In the anodization process, an electric field is applied to the zirconium alloy film 3a while it is immersed in a chemical conversion solution, and the electrolyte film 3 is formed from the zirconium alloy film 3a. The chemical conversion solution is, for example, an aqueous solution containing water, ammonium tartrate as an electrolyte, and ethylene glycol as a solvent. In this case, it is not desirable for the back surface of the porous insulating substrate 1 to come into contact with the chemical conversion solution. This is because the chemical conversion solution will permeate the back surface of the porous insulating substrate 1, and anodization will also occur at the interface between the porous insulating substrate 1 and the anode electrode 2.

[0040] In addition, since the periphery of the alloy region 32 is used as an electrode for power supply, it is necessary to create an interface between the gas and the chemical conversion solution inside the alloy region 32. Therefore, a jig 40 is used to isolate the alloy region 32 from the oxidized region 31. That is, after a part of the surface of the zirconium alloy film 3a is surrounded by the jig 40 as the oxidized region 31, only the oxidized region 31 is selectively immersed in the chemical conversion solution. In this state, an electric field is applied to the oxidized region 31 to form an electrolyte membrane 3 from the zirconium alloy film 3a in the oxidized region 31. The jig 40 is then removed.

[0041] The jig 40 is composed of an O-ring 41 and a protective film 42 that covers the periphery of the O-ring 41. The protective film 42 is provided at least between the zirconium alloy film 3a and the O-ring 41. If the jig 40 is composed of only the O-ring 41, the chemical conversion solution will locally infiltrate from the O-ring 41 during anodization at the interface between the gas and the chemical conversion solution, causing rapid oxidation and frequently causing corrosion of the alloy film, commonly known as "burning." Therefore, it is effective to protect the gas / liquid interface with the protective film 42. The protective film 42 is, for example, a resist film or an insulating film such as a silicon oxide film.

[0042] However, even if such a treatment is taken, local corrosion cannot be avoided. Also, holes are formed in the alloy region 32 at the location where the jig 40 contacts. If such a location exists, oxygen and hydrogen will directly combust without passing through the electrolyte membrane. To avoid this, only the chamber region 30 of the oxidation region 31, which is away from the location where the jig 40 is placed, is used as the solid oxide fuel cell 100.

[0043] Fig. 7 is a graph showing the current and voltage during anodization. Fig. 7 is also a graph showing the anodization of the zirconium alloy film 3a formed by a low-pressure sputtering method with a deposition pressure of 0.5 Pa or more and 1.0 Pa or less. Y is used as the rare earth element added to this zirconium alloy film 3a.

[0044] The anodization process is carried out in two stages: constant current mode and constant voltage mode. In the constant current mode, an oxidation current Ia is passed to grow an anodization barrier film. As the anodization barrier film grows, the resistance increases, so the oxidation voltage Va increases linearly. After the oxidation voltage Va reaches a predetermined value, the mode is switched to constant voltage mode.

[0045] In the constant voltage mode, the oxidation current Ia gradually decreases. This eliminates the unevenness in the thickness of the anodic oxide barrier film, and automatically repairs local defects. Ultimately, an anodic oxide barrier film with a nearly uniform thickness and no defects is obtained. Note that, in order to perform this constant voltage mode, it is necessary to leave the unoxidized Zr alloy on the base. If there is no base and the anode electrode 2 is exposed to oxidizing species (mainly O -2 ) will cause oxidation of the anode electrode 2 or generation of oxygen gas. In this case, the oxidation current Ia will not decrease and repair of the barrier film cannot be expected.

[0046] Thus, the chemical composition of the electrolyte membrane 3 obtained from the zirconium alloy film 3a formed by the low pressure sputtering method is (Y2O3) X (ZrO2) 1-X In this case, X=8%, and yttria-stabilized zirconia having a composition nearly close to 8YSZ was obtained. Also, the thickness of the electrolyte membrane 3 can be made 10 nm or more and 500 nm or less.

[0047] The zirconium alloy film 3a that has not been anodized, such as the alloy region 32, is oxidized to an oxide during assembly after the solid oxide fuel cell 100 is manufactured or during operation of the solid oxide fuel cell 100, and is subjected to heat treatment. That is, in a plan view, an oxide of the zirconium alloy film 3a formed by a method other than anodization is formed on the outer periphery of the electrolyte membrane 3. The chemical composition of the oxide of the zirconium alloy film 3a is different from that of the electrolyte membrane 3. In other words, the electrolyte membrane 3 contains a boundary that defines the anodization barrier film, that is, a boundary between the gas phase region and the liquid phase region in the anodization process. This liquid phase region is an anodization barrier film, and contains an electrochemical reaction region (chamber region 30) related to power generation.

[0048] In addition, in the oxidation region 31 (chamber region 30), it is ideal that the entire zirconium alloy film 3a is anodized, but as described above, the thickness of the zirconium alloy film 3a is set to be thicker than the desired thickness of the electrolyte membrane 3, taking into consideration the variation in thickness and the oxidation margin. Therefore, in the oxidation region 31 (chamber region 30), a part of the zirconium alloy film 3a may remain between the electrolyte membrane 3 and the anode electrode 2. In this case, as in the alloy region 32, the remaining zirconium alloy film 3a will later become an oxide.

[0049] Although the oxide of the zirconium alloy film 3a is different from ideal yttria-stabilized zirconia in terms of chemical composition and crystal state, it has oxygen ion conductivity. However, electronic insulation cannot be expected from the oxide of the zirconium alloy film 3a. Therefore, the oxide of the zirconium alloy film 3a can also function as a part of the electrolyte membrane 3, so that oxygen ions can reach the anode electrode 2. For example, if the thickness of the oxide of the zirconium alloy film 3a is about 10% of the thickness of the electrolyte membrane 3, there is almost no effect on the overall electrolyte characteristics.

[0050] 5, a conductive oxide film 4 and a cathode electrode 5 are successively formed by sputtering on the electrolyte membrane 3. In this manner, the solid oxide fuel cell 100 according to the first embodiment is manufactured.

[0051] (Embodiment 2) A solid oxide fuel cell 100 according to the second embodiment will be described below with reference to Figures 8 to 10. In the following description, differences from the first embodiment will be mainly described, and descriptions of points that overlap with the first embodiment will be omitted.

[0052] When attempting to obtain a thin electrolyte membrane 3, the anode electrode 2 may also be anodized during anodization because the thickness of the base zirconium alloy film 3a is thin. In the second embodiment, in order to protect the anode electrode 2, a stopper film 6 is provided between the anode electrode 2 and the electrolyte membrane 3 (zirconium alloy film 3a). For example, when the thickness of the electrolyte membrane 3 (the thickness of the zirconium alloy film 3a) is 10 nm or more and 100 nm or less, it is effective to provide the stopper film 6.

[0053] As shown in FIG. 8, a porous insulating substrate 1 is prepared in the same manner as in embodiment 1, a conductive film 1b is formed on the surfaces of the multiple holes 1a, and an anode electrode 2 is formed on the porous insulating substrate 1.

[0054] Next, a stopper film 6 is formed on the anode electrode 2 by a sputtering method. This sputtering method is performed under a film formation pressure of, for example, 10 Pa or more and 15 Pa or less. The stopper film 6 thus formed is made of a porous metal film. The thickness of the stopper film 6 is, for example, 5 nm or more and 50 nm or less.

[0055] The stopper film 6 is preferably a valve metal. The valve metal is selected from metals that can be anodized and whose oxide film exhibits oxygen ion conductivity and electronic insulation. Such valve metals are, for example, Ti, Mg, Al, Hf, Ta, or Zr. Since the stopper film 6 has such properties, the stopper film 6 can function as a part of the anode electrode 2.

[0056] As materials other than valve metals, materials constituting the conductive oxide film 4 are also effective. Since oxygen vacancies in the crystal of these materials are the carriers of electronic conductivity, it is expected that the supply of oxygen ions during anodization will cause the materials to lose their electronic conductivity and become highly resistive (electronically insulating).

[0057] Next, the zirconium alloy film 3a doped with a rare earth element is formed on the stopper film 6 by the same technique as in the first embodiment. In the second embodiment, the zirconium alloy film 3a has a thickness of 10 nm or more and 100 nm or less.

[0058] 9, a solid electrolyte film 3 is formed by anodizing the zirconium alloy film 3a in the same manner as in the first embodiment. Since the stopper film 6 is formed under the zirconium alloy film 3a, the stopper film 6 may be anodized, but the anode electrode 2 is protected from the anodization.

[0059] 10, a conductive oxide film 4 and a cathode electrode 5 are successively formed on an electrolyte membrane 3 in the same manner as in the first embodiment. In this manner, a solid oxide fuel cell 100 in the second embodiment is manufactured.

[0060] (Modification) A modification of the second embodiment will be described below.

[0061] In the first and second embodiments, the anode electrode 2 contains a transition metal such as Ni, but the anode electrode 2 of the modified example contains a precious metal. The precious metal is, for example, Pt. The anode electrode 2 of the modified example is formed by a sputtering method under a film formation pressure of 10 Pa or more and 15 Pa or less, and is made of a porous metal film.

[0062] If a noble metal is applied to the anode electrode 2 without the stopper film 6 formed as in the first embodiment, the noble metal is likely to be ionized and diffused during anodization, regardless of the thickness of the zirconium alloy film 3a. In other words, there is a risk that the anode electrode 2 may be destroyed. If the stopper film 6 is formed as in the second embodiment, such a problem can be prevented, and a noble metal can be applied to the anode electrode 2.

[0063] Although the present invention has been specifically described above based on the above embodiment, the present invention is not limited to the above embodiment and can be modified in various ways without departing from the spirit of the present invention. [Explanation of symbols]

[0064] 100 Solid oxide fuel cell 1. Porous insulating substrate 1a hole 1b Conductive film 2 Anode electrode 3 Electrolyte membrane 3a Zirconium alloy membrane 4. Conductive oxide film 5. Cathode Electrode 6 Stopper film 30 Chamber Area 31 Oxidation Region 32 Alloy area 40 Jig 41 O-ring 42 Protective film

Claims

1. A porous insulating substrate; an anode electrode formed on the porous insulating substrate; a solid electrolyte membrane formed on the anode electrode; a cathode electrode formed on the electrolyte membrane; Equipped with The solid oxide fuel cell, wherein the electrolyte membrane is a stabilized zirconia membrane doped with a rare earth element and also an anodization barrier membrane.

2. 2. The solid oxide fuel cell according to claim 1, A solid oxide fuel cell, wherein the electrolyte membrane has a thickness of 10 nm or more and 500 nm or less.

3. 2. The solid oxide fuel cell according to claim 1, The anode electrode of the solid oxide fuel cell is made of a porous metal membrane.

4. 4. The solid oxide fuel cell according to claim 3, a stopper film including a valve metal or a conductive oxide film between the anode electrode and the electrolyte membrane; The thickness of the electrolyte membrane is 10 nm or more and 100 nm or less, The anode electrode of the solid oxide fuel cell comprises a transition metal.

5. 4. The solid oxide fuel cell according to claim 3, a stopper film including a valve metal or a conductive oxide film between the anode electrode and the electrolyte membrane; The anode electrode of the solid oxide fuel cell comprises a precious metal.

6. 4. The solid oxide fuel cell according to claim 3, a conductive film formed on the surfaces of the plurality of holes formed in the porous insulating substrate,

7. 7. The solid oxide fuel cell according to claim 6, the electrolyte membrane is a yttria-stabilized zirconia membrane; the anode electrode includes Ni or Pt; the porous insulating substrate comprises anodized aluminum; The conductive membrane of the solid oxide fuel cell comprises Pt or Ni.

8. 2. The solid oxide fuel cell according to claim 1, In a plan view, the electrolyte membrane includes a boundary that defines the anodization barrier film, i.e., a boundary between a gas phase region and a liquid phase region in an anodization process; The liquid phase region is the anodized barrier film, and contains an electrochemical reaction region involved in power generation.

9. (a) providing a porous insulating substrate; (b) forming an anode electrode on the porous insulating substrate; (c) forming a rare earth element-added zirconium alloy film on the anode electrode; (d) performing an anodizing process on the zirconium alloy film to form a solid electrolyte film; (e) forming a cathode electrode on the electrolyte membrane; Equipped with The method for producing a solid oxide fuel cell, wherein the electrolyte membrane is a stabilized zirconia membrane to which the rare earth element is added and also an anodization barrier membrane.

10. 10. The method for producing a solid oxide fuel cell according to claim 9, The step (d) comprises: (d1) surrounding a portion of the surface of the zirconium alloy film as an oxidized region with a jig; (d2) selectively immersing only the oxidized region of the zirconium alloy film in a chemical conversion solution, and applying an electric field to the oxidized region to form the electrolyte membrane from the zirconium alloy film in the oxidized region; (d3) removing the jig after the (d2) step; The present invention relates to a method for producing a solid oxide fuel cell.

11. 10. The method for producing a solid oxide fuel cell according to claim 9, the zirconium alloy film and the anode electrode are each formed by a sputtering method; the sputtering of the zirconium alloy film is performed at a lower deposition pressure than the sputtering of the anode electrode; The anode electrode is made of a porous metal membrane.

12. 12. The method for producing a solid oxide fuel cell according to claim 11, The method for producing a solid oxide fuel cell, wherein the sputtering method for the zirconium alloy film is performed under a film formation pressure condition of 0.5 Pa or more and 1.0 Pa or less.

13. 12. The method for producing a solid oxide fuel cell according to claim 11, (f) between the step (b) and the step (c), a step of forming a stopper film including a valve metal or a conductive oxide film on the anode electrode; Further comprising: In the step (c), the zirconium alloy film is formed on the stopper film; The thickness of the zirconium alloy film is 10 nm or more and 100 nm or less, The method for producing a solid oxide fuel cell, wherein the anode electrode contains a transition metal.

14. 12. The method for producing a solid oxide fuel cell according to claim 11, (f) between the step (b) and the step (c), a step of forming a stopper film including a valve metal or a conductive oxide film on the anode electrode; Further comprising: In the step (c), the zirconium alloy film is formed on the stopper film; The method for producing a solid oxide fuel cell, wherein the anode electrode contains a precious metal.

15. 12. The method for producing a solid oxide fuel cell according to claim 11, (g) forming a conductive film on the surfaces of the plurality of holes formed in the porous insulating substrate between the steps (a) and (b); Further comprising: the electrolyte membrane is a yttria-stabilized zirconia membrane; the anode electrode includes Ni or Pt; the porous insulating substrate comprises anodized aluminum; The conductive film comprises Pt or Ni.

Citation Information

Patent Citations

  • Electrochemical reaction device and method for manufacturing electrochemical reaction device

    JP2015176774A